Risk factors for musculoskeletal injury in CrossFit: A systematic review - Mehrab, M.; Wagner, R. K.; Vuurberg, G.; Gouttebarge, V.; de Vos, R. J.; Mathijssen, N. M. C. (International Journal of Sports Medicine, 2023)
The objective of this systematic review was to identify potential risk factors for injury in CrossFit participants. Embase, Medline, Web of Science, Cochrane, CINAHL, Google Scholar, and SportDiscuss databases were all searched up to June 2021. Cohort studies that investigated risk factors for CrossFit injuries requiring medical attention or leading to time loss in sports were included. A best-evidence synthesis was performed combining all the outcomes from prospective cohort studies. From 9,452 publications identified, we included three prospective cohort studies from which two had a low risk of bias and one a high risk of bias. The studies examined 691 participants of whom 172 sustained an injury. There was limited evidence that switching between prescribed and scaled loads during training is associated with increased injury risk and that increased duration of participation is a protective factor for injury. This could mean that novice CrossFit athletes and those increasing their training load should have closer supervision by CrossFit coaches. These risk factors should be considered when developing preventive interventions.